Genetics of Congenital Heart Defects: The NKX2-5 Gene, a Key Player - Chung, Ill-Min (Genes (Basel), 2016)
Congenital heart defects (CHDs) represent the biggest fraction of morbid congenital anomalies worldwide. Owing to their complex inheritance patterns and multifactorial etiologies, these defects are difficult to identify before complete manifestation. Research over the past two decades has established firmly the role of genetics in the development of these congenital defects. While syndromic CHDs are more straightforward, non-syndromic CHDs are usually characterized by multiple mutations that affect intricate inter-connected developmental pathways. Knock-out and gene expression studies in mice and other genetic models have been performed to elucidate the roles of these implicated genes. Functional analysis has not been able to resolve the complete picture, as increasingly more downstream effects are continuously being assigned to CHD mutant factors. NKX2-5, a cardiac transcription factor, has received much attention for its role in cardiac dysmorphogenesis. Approximately 50 different mutations in this gene have been identified to date, and only a few have been functionally characterized. The mutant NKX2-5 factor can regulate a number of off-targets downstream to facilitate CHD development. This review summarizes the genetic etiology of congenital heart defects and emphasizes the need for NKX2-5 mutation screening.